Selecting model for treatmentof oily wastewater by MF-PAC hybrid process using mullite-alumina ceramic membranes - Mohsen Abbasi; Aboozar Taheri (Химия и технология воды, 2016)
Hermia’s models for cross flow filtration were used to investigate the fouling mechanisms of mullite-alumina ceramic membranes in treatment of oily wastewaters in a hybrid microfiltration-powdered activated carbon process (MF-PAC). Results show that cake filtration model can be applied for prediction of permeation flux decline for MF and MF-PAC process up to 400 ppm PAC. The complete pore blocking model and the intermediate pore blocking model can predict permeation flux decline with time for MF-PAC with 800 and 1200 ppm PAC respectively. Average error for prediction of permeation flux with cake filtration model is 2.19% for MF process and 2.16; 2.06 and 1.31% for MF-PAC process with 100; 200 and 400 ppm PAC respectively. Also for MF-PAC process with 800 and 1200 ppm PAC, average error for prediction of permeation flux with complete pore blocking model and intermediate pore blocking model was 6.11 and 6% respectively.